The Alignment of Technology and Structure through Roles and Networks - Barley, Stephen R. (Administrative Science Quarterly, 1990)
This paper outlines a role-based approach for conceptualizing and investigating the contention in some previous research that technologies change organizational and occupational structures by transforming patterns of action and interaction. Building on Nadel's theory of social structure, the paper argues that the microsocial dynamics occasioned by new technologies reverberate up levels of analysis in an orderly manner. Specifically, a technology's material attributes are said to have an immediate impact on the nonrelational elements of one or more work roles. These changes, in turn, influence the role's relational elements, which eventually affect the structure of an organization's social networks. Consequently, roles and social networks are held to mediate a technology's structural effects. The theory is illustrated by ethnographic and sociometric data drawn from a comparative field study of the use of traditional and computerized imaging devices in two radiology departments.